1999
DOI: 10.1080/104732299302440
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Characterization for Highway Construction Part I: Cut and Cover and Tunnel Finish Stages

Abstract: The purpose of this study was to characterize respirable dust, crystalline silica, diesel, and noise exposures to construction workers on a large highway construction project in Boston, Massachusetts. The study primarily focused on operating engineers and laborers, and to a lesser extent on ironworkers and carpenters during the tunnel finish and cut and cover stages. Full and partial shift noise dosimeter measurements were collected. Eighty percent of the 40 noise measurements were at or above 85 dBA, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…A study of US highway construction workers in 1994-95 found a mean concentration of 14 µg/m 3 elemental carbon (range 0.5-53 µg/m 3 , n = 14) in operating engineers working outdoors, mainly handling cranes, lifters, and earth movers. 17 The exposure was considerably higher for operating engineers during work in tunnels (mean 39 µg/m 3 ). The background concentration on the work site was fairly low (mean 3 and 6 µg/m 3 at two places, range 0.5-7).…”
Section: Discussionmentioning
confidence: 94%
“…A study of US highway construction workers in 1994-95 found a mean concentration of 14 µg/m 3 elemental carbon (range 0.5-53 µg/m 3 , n = 14) in operating engineers working outdoors, mainly handling cranes, lifters, and earth movers. 17 The exposure was considerably higher for operating engineers during work in tunnels (mean 39 µg/m 3 ). The background concentration on the work site was fairly low (mean 3 and 6 µg/m 3 at two places, range 0.5-7).…”
Section: Discussionmentioning
confidence: 94%
“…Two papers concerned with the cut and cover and Immersed Tube tunnels for the Boston Central Artery/Tunnel Project [8,9] are the only ones that the authors have discovered which report results for (6-hour) personal sampling for percussive concrete drilling (8-hour workdays), (Table 6). This is surprising, given its wide-spread use by civil engineering, building and building service contractors.…”
Section: Dust In Construction Elsewherementioning
confidence: 96%
“…In construction, Edelson et al 17 measured mean L Aeq levels for workers in the USA to be 89.8 dB. Other studies have shown that many trades within construction have the potential to be exposed to noise levels above 85 dB, [17][18][19][20][21][22] even those trades that may be expected to be low noise, such as electricians. 23 In agriculture, previous studies have documented high noise levels, frequently above 85 dB.…”
Section: Commentmentioning
confidence: 99%